Investigating the photocatalytic activity in bactericidal effect of iron(III) oxide bi-phase composite against Staphylococcus aureus - Dinh, Tan Muon; Loan, Nguyen Thanh; Nguyen, Hoang Hung; Cuong, Tran Viet; Dang, Vinh Quang; Huynh Tran My Hoa (Vietnam Journal of Science and Technology, 2026)
This work describes the phase transition process used to create a bi-phase composite (called “α/γ-Fe2O3”) from two iron precursors (FeSO4 and FeCl3). It was discovered that controlling the temperature between 200 and 800 C was effective in both producing γ-Fe2O3 nanoparticles and initiating the phase transition of γ-Fe2O3 into α-Fe2O3 nanoparticles. The formation of a bi-phase mixture (α/γ-Fe2O3) occurred at 500 C when the phase transition process was taking place. Consequently, the bactericidal efficiency of this bi-phase α/γ-Fe2O3 composite was more excellent than that of the single-phase α-Fe2O3 or γ-Fe2O3 material (from 1.1 to 1.6 times, respectively). Here, the bi-phase contacts probably formed between the α- and γ- phase nanoparticles of Fe2O3 played an important role in reducing the electron-hole recombination, and thus, increasing the photocatalytic and bactericidal efficiency of the developed composite material. Overall, our findings highlight the potential of this bi-phase material for practical photocatalytic applications.